FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENATAAN PKL SEBAGAI STRATEGI PENATAAN RUANG KOTA SURAKARTA - Murtanti Jani Rahayu; Rr. Ratri Werdiningtyas; Musyawaroh Musyawaroh (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2016)
Hunger and poverty countermeasure was appointed to be the first target in the Millennium Development Goals (MDGs) global mandate. It is relevant with Indonesia’s condition in the last three years in which the amount of poverty-stricken people grew significantly. To boost the population’s economy to a sustainable level, Solo’s City Government try to give more space to the informal sectors in the city. This policy doesn’t aim to improve the economy quantitatively but also equitably by facilitating the informal sectors, so that they can compete with the formal sectors that are dominated by the “big companies” as in nearly every big city in Indonesia.One of the growing informal sectors is the street vendors. Relocation and stabilization are the two programs run by the Surakarta government to give a better chance for the street vendors to survive the competition with the formal sectors. Hundreds even thousands of street vendors in Solo has been regulated to empower the city’s local economy. The factors that influence the success of the street vendor regulation isn’t only perceived from the city’s aesthetics, which always became the main reason, but also perceived from the quality growth in activity performance after the program has been done to ensure sustainability.The success of the street vendor regulation must be seen from the street vendor’s perspective. Unique character and street vendor behavior that vary richly must be known to ensure the street vendors can accept the planned program. In order to point out the location character role in the city’s spatial arrangement strategy, the focal point of this research is exploring the factors that influence street vendor regulation adjusting with the needs and demands of street vendors